The effects of tobacco smoking, and prenatal tobacco smoke exposure, on risk of schizophrenia: a systematic review and meta-analysis - Hunter, Abby; Murray, Rachael; Asher, Laura; Leonardi-Bee, Jo (Oxford University Press, 2018)
Introduction: The association between cigarette smoking and schizophrenia is well established. However, up to 90% of people with schizophrenia begin smoking before the onset of their illness, thus smoking could be an independent risk factor for schizophrenia. Prenatal exposure to maternal cigarette smoke is also associated with psychiatric problems in adolescence. Therefore, our aim was to undertake a systematic review and meta-analysis to explore the effect of smoking, and prenatal smoke exposure, on risk of schizophrenia. Method: We systematically searched Medline, Embase, PsychInfo, Maternity and Infant Care, and Web of Science (from inception to February 2018) to identify comparative observational studies of the risk of schizophrenia in relation to smoking status. Measures of Relative Risk (RR) were pooled in a meta-analysis with 95% confidence intervals, using random effects model. Results: Twelve studies (9 cohort, 3 case-control) were included. Odds ratios (OR) and hazard ratios (HR) were pooled together to estimate pooled RRs and estimates combined in a meta-analysis on an assumption of constant risk over time. Smokers had a significantly increased risk of schizophrenia compared to non-smokers (RR 1.99, 95% CI 1.10-3.61, I2= 97%, 5 studies). Exposure to prenatal smoke increased the risk of schizophrenia by 29% (95% CI 1.10-1.51, I2= 71%, 7 studies). Sensitivity analyses identified no significant differences between the results from studies reporting OR and HR. Conclusions: Our findings suggest smoking, and prenatal smoke exposure, may be an independent risk factor for schizophrenia. Care should be taken when inferring causation, given the observational nature of the studies.